Book Reviews - Irene Papoulis; Dan Mrozowski; Jacquelyne Kibler; Christy I. Wenger; Mary Leonard; Sharon Marshall (Journal of the Assembly for Expanded Perspectives on Learning, 2019)
Present and Feeling, Irene Papoulis Newkirk, Thomas. Embarrassment and the Emotional Underlife of Learning. Heinemann, 2017, Dan Mrozowski Young, Shinzen. The Science of Enlightenment: How Meditation Works. Sounds True, 2016, Jacquelyne Kibler Peary, Alexandria. Prolific Moment: Theory and Practice of Mindfulness for Writing. Routledge, 2018, Christy I. Wenger De Luca, Geraldine. Teaching toward Freedom: Supporting Voices and Silence in the English Classroom. Routledge, 2018, Mary Leonard Cooper, Brittney. Eloquent Rage, A Black Feminist Discovers Her Superpower, St. Martins, 2018, Sharon Marshall